(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Cannabis sativa L. is aware of a rich source of bioactive substances with various structures that exhibit pharmacological activity in the central nervous system, cardiovascular, cerebrovascular, respiratory, reproductive, and gastrointestinal systems. Materials and Methods: In this study, cannabis sugar leaves were soaked in 99% ethanol, followed by evaporation. The antibacterial effect of the cannabis sugar leaf extract was then evaluated using the disc diffusion method. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were determined using broth dilution. Results: The results of this study indicated that the cannabis sugar leaf extract inhibited Bacillus cereus, Vibrio cholerae, Escherichia coli, Staphylococcus aureus, and Staphylococcus epidermidis when compared to tetracycline, but it did not inhibit Pseudomonas aeruginosa. The MIC and MBC of the cannabis sugar leaves extract against B. cereus, V. cholerae, E. coli, S. aureus, and S. epidermidis were 0.977, 1.953, 31.25, 62.5, 125, 250, 250, 500, 250, and 500 mg/ml, respectively. The bioactive compounds in cannabis sugar leaf extract were identified using high-performance liquid chromatography. Conclusion: The results indicated that the major bioactive compounds were Δ-9- tetrahydrocannabinol (THC) and cannabidiol (CBD). While minor bioactive compounds included gallic acid and tannic acid. These results support the benefits of cannabis sugar leaf extract, which has been used for its pharmacological properties and may be useful as an alternative antimicrobial agent in medicine. J. Adv. Vet. Anim. Res., 12(1): 44–52, March 2025 http://doi.org/10.5455/javar.2025.l870